Pioneers, hidden champions, changemakers, and underdogs : lessons from China's innovators - Greeven, Mark J.; Yip, George S.; Wei, Wei, 1984 April 5- (Cambridge : The MIT Press, 2019)
An insider's view of China's under-the-radar, globally competitive innovators. Chinese innovators are making their mark globally. Not only do such giants as Alibaba and Huawei continue to thrive and grow through innovation, thousands of younger Chinese entrepreneurs are poised to enter the global marketplace. In this book, Mark Greeven, George Yip, and Wei Wei offer an insider's view of China's under-the-radar, globally competitive innovators. The authors, all experts on Chinese innovation, distinguish four types of innovators in China: pioneers , large companies that are globally known; hidden champions , midsize enterprises that are market leaders in their niches; underdogs , technology-driven ventures with significant intellectual property; and changemakers , newer firms characterized by digital disruption, exponential growth, and cross-industry innovations. They investigate what kinds of innovations these companies develop (product, process, or business model), their competitive strategies, and key drivers of innovation. They identify six typical ways Chinese entrepreneurs innovate, including swarm innovation (collectively pursuing opportunities) and rapid centralized decision making. Finally, they look at how Chinese innovators are going global, whether building R&D networks internationally or exporting disruptive business models. The book includes many examples of Chinese innovators and innovations, drawn from a range of companies--from pioneers to changemakers--including Alibaba, Haier, Hikvision, Malong Technology, Weihu Solar, Mobike, and Cheetah Mobile. Greeven, Yip, and Wei offer an essential guide to what makes China a heavyweight competitor in the global marketplace.
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; Technological innovations -- Economic aspects -- China; New business enterprises -- China; New products -- China; Entrepreneurship -- China